2020
DOI: 10.20473/jbe.v8i12020.16-25
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of Noma in Papua Province in 2017

Abstract: Background: Indonesia Ministry of Health in October 2017 obtained information from the Public Health Emergency Operation Center (PHEOC) that there allegations of noma case in a toddler from the Korowai tribe in Asmat District. Purpose: This study aims to describe the magnitude of the noma problem, identify risk factors, and find other noma cases for prevention and control. Methods: This was a descriptive study using a case study approach. Primary data was obtained from interviews with family or close relatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This situation reflects the low level of welfare of the Papuan people so that it needs attention and also the lack of studies examining this issue. Several previous studies, such as Pudjohartono, et al (2019), Kaimudin & Hidajah (2020), Hasanah et al (2020), and Wulandari et al (2022) are still local and reactive to an extraordinary event, only descriptive and did not carry out an in-depth analysis of the factors that cause malnutrition.…”
Section: Introductionmentioning
confidence: 95%
“…This situation reflects the low level of welfare of the Papuan people so that it needs attention and also the lack of studies examining this issue. Several previous studies, such as Pudjohartono, et al (2019), Kaimudin & Hidajah (2020), Hasanah et al (2020), and Wulandari et al (2022) are still local and reactive to an extraordinary event, only descriptive and did not carry out an in-depth analysis of the factors that cause malnutrition.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, several studies have shown that in countries where the condition is widespread, risk factors such as malnutrition, debilitating diseases like malaria and measles, close residential proximity to livestock are reported (44) (45). Moreover, respiratory or diarrheal syndrome and an altered oral microbiota have been reported as potential risk factors of Noma.…”
Section: Discussionmentioning
confidence: 99%
“…In this 5 year old child, risk factors such as malnutrition and poor oral hygiene contributed to the occurrence of noma. 10 Because the case is rarely found in Indonesia, it could be possible that cases of noma will be unidentified due to lack of knowledge about this disease.…”
Section: Literature Review Epidemiologymentioning
confidence: 99%